Infertility-related distress and female sexual function during assisted reproduction. Issue 6 (15th May 2019) - Facchin, Federica; Somigliana, Edgardo; Busnelli, Andrea; Catavorello, Anita; Barbara, Giussy; Vercellini, Paolo
Abstract: STUDY QUESTION: Is infertility-related distress a risk factor for impaired female sexual function in women undergoing assisted reproduction? SUMMARY ANSWER: Infertility-related distress, and especially social, sexual, and relationship concerns, is associated with female sexual dysfunction. WHAT IS KNOWN ALREADY: Women with infertility are more likely to present sexual dysfunction relative to those without infertility. Moreover, assisted reproduction is associated with increased risk for female sexual problems. To date, this higher proportion of sexual impairment in infertile women has been simplistically linked to the stress associated with the condition and investigated risk factors included mainly demographic and clinical variables. Quantitative studies aimed at identifying risk factors for sexual dysfunction that also included the evaluation of infertility-related distress are conversely lacking. STUDY DESIGN, SIZE, DURATION: This observational study was conducted at the Infertility Unit of the Fondazione Ca' Granda, Ospedale Maggiore Policlinico of Milan between 2017 and 2018. PARTICIPANTS/MATERIALS, SETTING, METHODS: We included 269 consecutive patients with infertility aged 24–45 (37.8 ± 4.0 years). Sexual function outcomes were sexual dysfunction (assessed with the Female Sexual Function Index), sexual distress (evaluated with the Female Sexual Distress Scale-Revised), dyspareunia, and number of intercourses in the month preceding ovarian stimulation. Infertility-related distress was measured with the Fertility Problem Inventory (FPI). The effects of potential confounders such as demographic variables (women's and partners' age and level of education) and infertility-related factors (type and cause of infertility, number of previous IVF cycles, and duration of infertility) were also examined. MAIN RESULTS AND THE ROLE OF CHANCE: Women with higher infertility-related distress were more likely to report sexual dysfunction (odds ratio = 1.02 per point of score; 95% CI, 1.01–1.03; P =  0.001). Three FPI domains (i.e. social, relational, and sexual concerns) were correlated with almost all sexual function outcomes ( Ps <  0.05). LIMITATIONS, REASONS FOR CAUTION: Women who were not sexually active were not included, thus reasons for sexual inactivity should be further explored in future studies. Data regarding men (e.g. sexual function and infertility-related distress) were lacking, thus cross-partner effects were not examined. Recall bias (also due to the fact that questionnaires were administered on the day of oocytes retrieval) and social desirability bias may have also affected women's responses to the questionnaires. WIDER IMPLICATIONS OF THE FINDINGS: Social, relational, and sexual concerns should be assessed and addressed in psychological counselling with the infertile couple. STUDY FUNDING/COMPETING INTEREST(S): None. TRIAL REGISTRATION NUMBER: Not applicable.